Manajemen Gerakan Sekolah Menyenangkan dalam Penguatan Pendidikan Karakter (PPK) di SD Negeri Buayan Kebumen - Burhan Nudin; Tyas Prayesti; Suratiningsih Suratiningsih; Wahyu Dwi Novianty (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2020)
Gerakan Sekolah Menyenangkan (GSM) i.e Enjoyable School Movement, actively participates in the creation of an adaptive educational culture with changing times. This research aims to analyze GSM management in Penguatan Pendidikan Karakter (PPK) i.e Character Building Affirmation in Buayan 1 Kebumen Elementary School. This is descriptive-qualitative research. The data were collected through interviews, observations, and documentation. The results show that GSM management in Buayan 1 Kebumen Elementary School uses the following functions: 1) Planning with carefully in elaborating GSM principles by school resources; 2) Organizing, with the formation of work divisions explained in detail according to authority and duties; 3) Implementation through the establishment of a 'learning environment' which provides physical and emotional development space for students; 4) Supervision by analyzing strengths, weaknesses, supporting and inhibiting factors for future program improvement references. GSM has become the right program to be developed as a solution to the imbalance in the quality of education so far through grassroots transformation.